GLT-1 Knockdown Inhibits Ceftriaxone-Mediated Improvements on Cognitive Deficits, and GLT-1 and xCT Expression and Activity in APP/PS1 AD Mice - Gao, JunXia; Liu, LiZhe; Liu, Chao; Fan, ShuJuan; Liu, LiRong; Liu, ShuFeng; Xian, Xiao-Hui; Li, Wen-Bin (Frontiers in Aging Neuroscience, 2020)
Objective: Glutamate transporter-1 (GLT-1) and system xc– mediate glutamate uptake and release, respectively. Ceftriaxone has been reported to upregulate GLT-1 expression and improve cognitive decline in APP/PS1 mice. The aim of the present study was to elucidate the role of GLT-1 in ceftriaxone-mediated improvement on cognitive deficits and associated changes in xCT (catalytic subunit of system xc–) expression and activity using GLT-1 knockdown APP/PS1 mice. Methods: GLT-1 knockdown (GLT-1+/–) mice were generated in C57BL/6J mice using CRISPR/Cas9 technique and crossed to APP/PS1 mice to generate GLT-1+/–APP/PS1 mice. The cognition was evaluated by novel object recognition and Morris water maze tests. GLT-1 and xCT expression, GLT-1 uptake for glutamate, and glutathione levels of hippocampus were assayed using western blot and immunohistochemistry, 3H-glutamate, and glutathione assay kit, respectively. Results: In comparison with wild type mice, APP/PS1 mice exhibited significant cognitive deficits, represented with poor performance in novel object recognition and Morris water maze tests, downregulated GLT-1 expression and glutamate uptake. Ceftriaxone treatment significantly improved the above impairments in APP/PS1 mice, but had negligible impact in GLT-1+/–APP/PS1 mice. The xCT expression increased in APP/PS1 and GLT-1+/–APP/PS1 mice. This upregulation might be a compensatory change against the accumulated glutamate resulting from GLT-1 impairment. Ceftriaxone treatment restored xCT expression in APP/PS1 mice, but not in GLT-1+/–APP/PS1 mice. Glutathione levels decreased in APP/PS1 mice in comparison to the wild type group. After ceftriaxone administration, the decline in glutathione level restored in APP/PS1 mice, but not in GLT-1+/–APP/PS1 mice. Conclusion: Ceftriaxone improves cognitive impairment of APP/PS1 mice by upregulating GLT-1-mediated uptake of glutamate and co-regulation of GLT-1 and xCT in APP/PS1 mice.